REGENERASI PETANI BAGI KEBERLANJUTAN PEMBANGUNAN PERTANIAN DI KABUPATEN BANTUL - , TIRTA PERWITASARI; , Ir. Roso Witjaksono, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted in Pandak sub-district and Sanden sub-district, Bantul district with the purpose of finding out: 1) the farmers motivation to continue farming activities, 2) the factors which affects farmers motivation to continue farming activities, and 3) the process of farmers and agricultural regeneration for sustainability of agricultural development in Bantul district. The method used in this research was descriptive which was done by doing survey. The process of choosing the sub-district, villages and farmer groups as sample were done purposively, while the process of choosing the farmers were done randomly. The number of total sample was 60 farmers consisted of 30 farmers from the Sanden sub-district and 30 farmers from the Pandak sub-district. The analysis methods which were used were proportion test and multiple linear regression analysis. The results of this research showed that farmers motivation to continue farming considered as motivation in high category. Farmerâs age affects the farmers motivation to continue farming activities in negative way, while the capital resources and job orientation has positive effect farmers motivation to continue farming. Factors that did not significantly affect the farmers motivation to continue farming were farmers education, land size, land status, capital quantity, farming income, farming income contribution, perception, status of employment as a farmer, another jobs, parents motivation, commodities, and role of extension worker. Farmers regeneration included low category, and agricultural regeneration had good prospect if only the land size of agriculture could be defended.